EFFECTIVENESS OF EARLY SEPSIS RECOGNITION AND TIMELY INTERVENTION IN IMPROVING PATIENT OUTCOMES IN THE EMERGENCY DEPARTMENT OF A RESOURCE-LIMITED SETTING (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Sepsis is a major cause of morbidity and mortality in emergency settings. Early recognition and intervention are critical in improving patient outcomes, yet delayed diagnosis and treatment remain significant challenges, particularly in resource-limited settings. This study evaluates the impact of early sepsis recognition and prompt therapeutic interventions on patient outcomes in the emergency department at Venkareshwara Medical College, Pondicherry, India. Objective: The study aimed to prospectively assess the effectiveness of early sepsis recognition using the Quick Sequential Organ Failure Assessment (qSOFA) score and lactate levels, along with timely administration of antibiotics and intravenous fluids, in improving 30-day mortality rates, reducing organ dysfunction, and shortening hospital stays. Methods: This prospective observational study was conducted over 12 months, enrolling 120 adult patients who met Sepsis-3 criteria for sepsis. The patients were divided into early intervention (treatment within the first hour of sepsis recognition) and delayed intervention (treatment after the first hour) groups. Outcomes were measured in terms of 30-day mortality, incidence of organ dysfunction, length of hospital stay, and vasopressor use. Data were analyzed using descriptive statistics and comparison of groups was performed using chi-square and t-tests. Results: The early intervention group showed significantly lower 30-day mortality (18%) compared to the delayed intervention group (42%) (p < 0.01). The mean time to fluid resuscitation and antibiotic administration was significantly shorter in the early intervention group (58 minutes for fluids and 65 minutes for antibiotics) compared to the delayed group (133 minutes for fluids and 138 minutes for antibiotics). The incidence of organ dysfunction was lower in the early intervention group (45% vs. 65%, p < 0.05), and the average length of hospital stay was shorter (5 days vs. 8 days, p < 0.01). Vasopressor use was also lower in the early intervention group (10% vs. 35%, p < 0.05). Conclusions: Early recognition and prompt intervention significantly reduce 30-day mortality, organ dysfunction, and hospital stay length in sepsis patients. The use of clinical decision-making tools like qSOFA and lactate monitoring can enhance early sepsis detection and management, particularly in resource-constrained settings. This study highlights the need for continued emphasis on early sepsis protocols in emergency care.